A Modified Thromboplastin Screening Test - Macpherson, Janet C.; Hardisty, R. M (Thrombosis and Haemostasis, 1961)
A modification of the thromboplastin screening test of Hicks and Pitney is described, in which the effect of surface contact on the test plasma is controlled by the addition of a suspension of kaolin to the incubation mixture before recalcification.Comparative studies show the modified test to give more reproducible results than the standard method.